The investigation of thermo-responsive polymers exhibiting LCST with interactions between water molecules by quantum mechanical methods - Kütük Can, Fatma (Graduate School, 2022)
Thermo-responsive polymers exhibiting the coil-to-globule phase transition at the lower critical solution temperature (LCST) have been the subject of great interest in the development of smart materials. As a result of LCST behavior in aqueous solutions, the polymers undergo a phase separation in water upon heating, resulting in a decreased solubility and a change in conformation from hydrated coil to collapsed globular for diluted solutions. In this work, thermo-responsive polymers in aqueous solutions have been studied in terms of their conformational changes which plays a crucial role in determining the role of functional groups and their interactions with water. Poly (N-isopropylacrylamide) (PNIPAAm), Poly(N-vinylisobutyramide)(PNVIBA), and Poly(2-ethoxyethyl vinyl ether)(PEOVE) exhibiting LCST behavior in water were studied in order to examine structural changes by using Density Functional Theory (DFT). Geometry optimizations were carried out using the B3LYP functional and 6-31G(d,p) basis set, which are known to perform well in the geometry optimizations of organic molecules. The hydrogen bond interaction of the water molecule with the pentamer of these monomers, which is the longest oligomer chain optimized starting from the dimer molecules, was modeled by testing various configurations. Interaction energies were calculated by using different functionals such as B3LYP, LC-wPBE and CAM-B3LYP and 6-311G(2df,2pd) basis set for a quantitative interpretation of the hydrogen bond. The basis set superposition error (BSSE) was also considered in all interaction energy calculations. Interaction energies were also corrected by the addition of zero point energies (∆ZPE). The effect of segment...solvent and segment...segment interactions on the conformation of the polymer chain were investigated in solvent media. The effect of the size of the oligomer on the conformation was also studied. In order to observe conformational changes in the backbones, Radius of gyration (Rg) and Root-mean-square deviation (RMSD) were calculated between the oligomer-water complexes and the unhydrated oligomer chain. The calculations in this study aim to provide insight into the effect of intermolecular interactions on conformational transitions in single chains of thermo-responsive polymers. Based on our calculations, the increasing number of water molecules results in an increase in the strength of the interaction.
LCST davranışı gösteren ısıya duyarlı polimerlerin su ile etkileşimlerinin kuantum mekanık yöntemlerle incelenmesi
Thesis (M.Sc.) -- İstanbul Technical University, Graduate School, 2022
Keywords: polymers; polimerler; quantum mechanics; kuantum mekaniği; interaction; etkileşim